DIMENSI HUKUM DAN CAGAR BUDAYA (KRITIS, 2022)
In the cultural heritage management, the legal aspect is vital as it has the functions of qualification, setting policy directions, legitimizing tools, regulating and enforcing laws and sanctions. This essay will focus on how dimensions of law are related to culture in Indonesia, the paradigm shift in the management of cultural culture which is also adopted by Indonesia, as well as raises certain problems as interactions and changes at the empirical level.